Composition, abundance and distribution of rodent species in Alemsaga Priority State Forest and farmlands, northwestern Ethiopia. (7th March 2022) - Takele, Bewketu; Yihune, Mesele; Bekele, Afework
Abstract: The aim of this study was to investigate species composition, relative abundance, habitat preference and seasonal variations of rodents in Alemsaga Priority State Forest and the nearby farmlands. A total of 1311 individual rodents were captured in six permanent grids and line transects, comprising of nine species, namely Lophuromys simensis, Arvicanthis abyssinicus, Desmomys harringtoni, Mastomys natalensis, Stenocephalemys albipes, Rattus rattus, Arvicanthis dembeensis, Mus musculus and Acomys cahrinus . Hystrix cristata and Tachyoryctes splendens were also recorded but not captured in trapes. About 44.4% of captured species are endemic to Ethiopia. Lophuromys simensis was captured from all habitats, while Acomys cahrinus was recorded only in Carissa land. The highest abundance of rodents was recorded in crop fields and the lowest in Carissa land. The overall trap success was 14.76%. Statistical variation was observed between individual rodent species among different habitats. Highest rodent populations were recorded during the wet season. Females comprised more individuals than males. Adults outnumbered sub‐adults and juveniles. Vegetation composition, altitudinal variations and human disturbance were the major factors affecting the distribution of rodents in the area. Attention should be given by the local administrators to conserve the area. Résumé: Le but de cette étude était d'étudier la composition des espèces, l'abondance relative, les préférences. en matière d'habitat et les variations saisonnières des rongeurs dans la forêt domaniale d'intervention prioritaire d'Alemsaga et les terres agricoles adjacentes. Au total, 1 311 rongeurs individuels de neuf espèces, à savoir Lophuromys simensis, Arvicanthis abyssinicus, Desmomys harringtoni, Mastomys natalensis, Stenocephalemys albipes, Rattus rattus, Arvicanthis dembeensis, Mus musculus et Acomys cahrinus ont été capturés sur six grilles et transects linéaires. Les espèces Hystrix cristata et Tachyoryctes splendens ont également été signalées mais n'ont pas été capturées dans les pièges. Environ 44, 4% des espèces capturées sont endémiques en Éthiopie. Lophuromys simensis a été capturé dans tous les habitats, tandis qu'Acomys cahrinus n'a été signalée que dans les terres de Carissa. La plus forte abondance de rongeurs a été enregistrée dans les champs cultivés et la plus faible dans les terres de Carissa . Le succès global du piège était de 14, 76 %. Une variation statistique a été observée entre différentes espèces de rongeurs dans différents habitats. Les populations de rongeurs les plus importantes ont été constatées pendant la saison des pluies. Le nombre d'individus femelles était plus élevé que celui des individus mâles. Les individus adultes étaient plus nombreux que les individus non‐adultes et juvéniles. La composition de la végétation, les variations d'altitude et les perturbations humaines étaient les principaux facteurs affectant la répartition des rongeurs dans la région. Une attention doit être accordée à ces résultats par les administrateurs locaux aux fins de conservation de la région.